Phagocytosis by macrophages decreases the radiance of bioluminescent Staphylococcus aureus - Elles C. Boonstra; Liliana Agresti; Henny C. van der Mei; Paul C. Jutte; Jelmer Sjollema (BMC Microbiology)
Abstract Background In vivo evaluations of the antimicrobial efficacy of biomaterials often use bioluminescent imaging modalities based on bioluminescent bacteria to allow follow-up in single animals. Bioluminescence production by bacteria is dependent on their metabolic activity. It is well known that several factors can influence the metabolism of bacteria, such as the use of antimicrobials and changes in bacterial growth phase. However, little is known about the influence of intracellular residence of bacteria on bioluminescence. For example, Staphylococcus aureus can survive in the peri-implant tissue and is known to survive intracellularly in macrophages. Results In this study, we evaluated the bioluminescent radiance of S. aureus upon phagocytosis by macrophages. We showed that S. aureus reduced its bioluminescence upon phagocytosis by macrophages compared to S. aureus in a single culture. Simultaneously, bacterial numbers as measured by colony-forming units remained constant over time. S. aureus was released extracellularly as a result of macrophage cell death. Following this release, the bacteria increased their bioluminescence again. Replenishment of fresh macrophages showed an immediate increase in bioluminescence. Moreover, the addition of fresh macrophages showed a diminished decrease in bioluminescence at 24 h of coculture, but this effect did not last. Conclusion Together, this study demonstrates that phagocytosis by macrophages decreases bioluminescence of S. aureus, which is an important factor to consider when using bioluminescent imaging to study the infection process in an in vivo model.